A hundred years later: Zou Xueping's documentaries and the legacies of China's New Culture Movement. Issue 2 (3rd May 2016) - Pickowicz, Paul G.
ABSTRACT: One of the ambitious goals of the famous New Culture Movement launched in 1915 was the democratization of cultural production in China. This meant promoting independent and critical works by writers and artists of all sorts. The movement met stiff, sometimes overwhelming, resistance both before and after 1949. Since the early 1950s, socialist state-directed cultural production has dominated, but the legacies and goals of the original New Culture Movement continue to resurface. This essay locates recent efforts of Zou Xueping, a young, female, independent, documentary filmmaker, in the larger context of the century-old determination to foster the democratization of Chinese cultural production. Zou does this by returning to her home village in Shandong to explore the relationship between past and present. On the one hand, she asks very old people to remember the awful traumas of the Great Famine of the late 1950s and early 1960s, while on the other she mobilizes very young people to take direct action to confront a range of problems that plague the village in the present day. Her works asks interesting questions about how independent artists encourage the agency of their subjects and how the democratization of culture stimulates healthy debate and grassroots initiatives.